The Influence Of Green Accounting, Corporate Social Responsibility Disclosure, And Firm Size On Firm Value - Resini, Luh Sintya; Mimba, Ni Putu Sri Harta (International Journal Labs, 2025)
Firm value is the achievement of a company's success as seen by investors who are related to stock prices. When the firm value increases, investors will trust to invest in the company. The purpose of this study is to obtain empirical evidence of the influence of green accounting, including corporate social responsibility, and company size on company value. Stakeholder and signal theories are used to underlie the analysis and interpretation of the results of this study. This research was conducted in energy sector companies listed on the Indonesia Stock Exchange. This study fills the gap in the 2021-2024 period. The sample determination was carried out using a purposive sampling technique. Firm value is measured using the Tobin's Q ratio and a sample of 260 observations was obtained. The data analysis technique used is Multiple Linear Regression Analysis. The results of the study show that Green Accounting has a negative effect on company value, Corporate Social Responsibility Disclosure has a positive effect on company value, and Company Size has a positive effect on company value.